106 IMPROVED VENTILATION IN PIGLETS TREATED WITH NASAL INTERMITTENT POSITIVE PRESSURE VENTILATION VERSUS SYNCHRONIZED INTERMITTENT MANDATORY VENTILATION. (1st January 2006) - Lampland, A. L.; Meyers, P. A.; Worwa, C. T.; Swanson, E. C.; Mammel, M. C.
Abstract : Background: Nasal intermittent positive pressure ventilation (NIPPV) is used to augment continuous positive airway pressure but there is little information regarding its efficacy. Hypothesis: Surfactant deficient piglets treated with NIPPV would have improved physiologic tolerance of non-invasive assisted ventilation and decreased inflammatory markers than those treated with synchronized intermittent mandatory ventilation (SIMV). Methods: Two modes of assisted ventilation, NIPPV and SIMV, were compared in spontaneously breathing piglets with saline lavage induced lung injury (PaO2 < 100 torr in FiO2 1.0 for minimum of 15 minutes). Both modes were provided using the Dräger Babylog 8000. Animals were randomized to NIPPV (n = 12) or SIMV (n = 11) and were treated for 6 hours. SIMV settings were VT 8 mL/kg, PEEP 5, and rate 20. NIPPV settings were PIP 30, PEEP 5, and rate 20. Oxygen was adjusted to maintain PaO2 of 80-100 torr; PIP and rate were adjusted to alter PaCO2. Physiologic parameters and arterial blood gases were continuously monitored. Data were recorded prior to lung injury, once lung injury was achieved, and then hourly. After 6 hours of treatment, piglets were euthanized. Lung tissue was then obtained to analyze for evidence of lung inflammation, including myeloperoxidase, interleukin-8, and hydrogen peroxide levels. Inflammatory marker data were analyzed using the Kruskal-Wallis test. Physiologic data were analyzed using ANOVA. Results: Inflammatory marker levels were not significantly different between the two groups. Piglets treated with NIPPV demonstrated improved arterial blood gas pH (p < .001), improved pCO2 (p = .05), and a lower set respiratory rate (p < .0001) as compared to the SIMV-treated piglets. Total respiratory rate was not different. However, the SIMV group had a lower PIP (p < .001) and improved a-A gradient (p < .001) when compared to the NIPPV group. Heart rate, mean blood pressure, and mean airway pressure were not significantly different between the groups. Conclusion: Surfactant deficient piglets treated with NIPPV demonstrated more efficient gas exchange with proportionally fewer mechanical breaths. In surfactant deficient piglets, NIPPV offers an adequate and non-invasive ventilatory strategy.